Implementasi Pelayanan Publik Di Dinas Pariwisata Di Kota Jambi - Dedek Kusnadi (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2023)
Implementation of Public Service is all services organized by public service providers as an effort to meet the needs of service recipients and implementers of legislation. Public service is basically about the vast aspects of life. In the life of the state, the government has the function of providing various public services required by the community. One thing that until now is often still a problem in the relationship between the people and the government in the region is in the field of public services, especially in terms of the quality or quality of service government apparatus to the community.Tourism is currently being intensively incentive in the city of Jambi. Lots of local and foreign tourists visiting the city of Jambi. But with the level of service is said to be less than the relevant Office to make the process of tourism is not going well.In this research used qualitative research method, so the researcher will not specify the research only based on research variable, but the whole social situation examined covering aspect of place, actors and activity that interact synergistically. The result of the research shows that the lack of public service available in the Jambi City Tourism Office makes the tourism process less good. With the level of human resources that have not qualified with the limitations of foreign language skills make the tourists, especially foreign tourists feel uncomfortable. The tourism program created by the government itself has not been fully felt directly by the community. Lack of socialization of the existence of tourism programs from the government to make people less aware of the importance of existing tourism.